If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9m + 23 = -4 Reorder the terms: 23 + 9m = -4 Solving 23 + 9m = -4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + 9m = -4 + -23 Combine like terms: 23 + -23 = 0 0 + 9m = -4 + -23 9m = -4 + -23 Combine like terms: -4 + -23 = -27 9m = -27 Divide each side by '9'. m = -3 Simplifying m = -3
| 6c-24d+cx-4dx= | | 6x-2y=19 | | 6-12=4w-w | | log[5](2x)=log[5](x+6)+log[5](4) | | -7d=77 | | 6-12=4w-4 | | 15=r/-2 | | 2x-3x+6=10-14+x | | 1/6x-1/9(2x-3)=1 | | 2(4x+8)=-32 | | 8+2.5x=10+x | | 3ydx=2xdy | | 4+1/2x=13 | | 3-2a(a-1)=a(3-2a)-(2a-3) | | -20-(4h-1)=31 | | X+.06x=40 | | y=-3(x-2)(x-7) | | 19a-18a+7=-13 | | -6(2+6x)=-120 | | 3x^9y^7+6x^7y^6+9x=0 | | -5(2m-4n)= | | 1/2(8h)=36 | | 6+6(2x-1)=12x | | 2/v=1/8 | | -17=-13-6(4b+20) | | (y-8)+24=3(y-6) | | 15t+6t-11t=150 | | 7x-12x+31x+15x=+12-8 | | (x+59)+(x+51)+84=180 | | -12v+16=4(-3v+4) | | m+5-4=18 | | 5x-2=(14/3) |